FORMULASI PEMBELAJARAN MATEMATIKA BAGI ANAK TUNAGRAHITA - Natasya D.P, Erika Marsi, Meidawati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
This study aims to determine the learning formulation that is suitable for students with mental disabilities. This type of research is qualitative research. Data analysis uses the process of data reduction, data presentation, and conclusion drawing. Planning mathematics learning for mentally disabled children at BC SLB Hamong Putro uses the 2013 curriculum implementation plan (RPP). The learning process of mathematics for mentally disabled children contains several aspects, namely the material taught is material learning that is concrete to material that is abstract, then positive giving reinforcement so that students are enthusiastic in learning, besides learning programs that are given to students individually, after that the learning evaluation process is carried out to find out the ability of students, then the material conveyed must be material that supports the achievement of set goals, and the material conveyed must be material that is useful for everyday life. The evaluation and follow-up steps that must be done are the preparation of an Individual Learning Program (PPI) and follow-up activities after conducting an evaluation in the form of special guidance carried out by teachers for mentally disabled students.